INSULIN/IGF/FOXO SIGNALING IN STEM CELLS AND AGING. (11th November 2018) - Webb, A
Abstract: FOXO transcription factors are conserved regulators of longevity downstream of insulin/IGF signaling. FOXOs regulate a number of cellular processes, including metabolism, protein quality control, the cell cycle, and oxidative stress. However, the mechanisms by which these transcriptional regulators regulate these various processes in order to maintain cellular homeostasis remain unclear. We have used a genomics approach to uncover the direct networks regulated by FOXO transcription factors in various species and across cell types in the mouse. Moreover, through in vivo work and cell culture models, we found that FOXOs are critical for the maintenance of stem cell homeostasis in mammals, which is critical for maintaining healthy pools of stem cells during aging, and for reducing tumorigenicity of cancer stem cells. Together, this work provides new insight into how FOXOs directly regulate conserved programs of target genes to support healthy aging across species.